TRANSFORMASI GENERASI MUDA SAWAH LADANG MELALUI INOVASI TEKNOLOGI AIR BERSIH DAN PEMBIBITAN IKAN DI NAGARI MAGEK, SUMATERA BARAT - Saputro, Dendi Adi; Haris, Sabri; Ridwan, Ridwan; Satria, Eka; Havendry, Adly; Pratoto, Adjar; Dahlan, Hendery; Augia, Trisfa (Jurnal ABDI: Media Pengabdian Kepada Masyarakat, 2026)
Nagari Magek, located in Kamang Magek District, Agam Regency, West Sumatra, faces serious problems related to clean water quality due to the high iron, manganese, and sulfur content. Although a solar-powered borehole system has been built to meet the water needs of 300 households, the water produced is still unfit for consumption. It impacts the decline of fish breeding businesses, one of the essential local traditions in Nagari Magek. To overcome this problem, community service activities aim to design effective clean water treatment technology and assist in fish nurseries and farming. The design process of the multi-level water filter has been carried out as a solution to improve water quality by introducing aeration-sedimentation-filtration technology and the Recirculating Aquaculture System (RAS) system. In addition, the fish nursery business in Nagari Magek is supported by modern pond management training and the empowerment of the younger generation for sustainable management.